Microbiological and micro‐computed tomography analysis of natal teeth: a case report - Silva-Sousa, Alice Corrêa; Silva-Sousa, Yara Teresinha Corrêa; Pitondo-Silva, André; Nakamura-Silva, Rafael; Tavella-Silva, Nathalia Cristina; Danelon, Marcelle (ARCHIVES OF HEALTH INVESTIGATION, 2021)
The aim of this study was to report a clinical case of a natural tooth found in a 1-day-old newborn, its clinical implications and proper management. The female patient was referred by a pediatrician who contacted the University of Ribeirão Preto Pediatric Dentistry Clinic (UNAERP, Ribeirão Preto, Brazil), informing that the patient with 40 hours of life, still in the maternity ward, had a foreign body in the oral cavity since birth, which was bothering the mother at the time of breastfeeding. At clinical examination, the presence of a Christmas tooth with grade 3 mobility was observed. After one month of life, it was possible to perform a radiographic examination, which resulted in the definitive diagnosis of the Christmas tooth, and the proposed treatment was the surgical removal of the dental element and subsequent follow-up. Prior to surgical removal, the biofilm present on the coronary surface was aseptically collected for microbiological analysis consisting of isolating the bacteria in different culture media and identifying them by sequencing 16S rRNA. The extracted tooth was scanned in high-resolution microtomography, reconstructed, and qualitatively analyzed. Microbiological analyses showed the presence of two bacterial species Streptococcus salivarius and Staphylococcus hominis, both species considered saprophytes, being part of the oral microbiota. The knowledge of this anomaly and the training of dentists to perform an accurate diagnosis, as well as the importance of multidisciplinary work, are of extreme relevance.